2015
DOI: 10.1093/fampra/cmv062
|View full text |Cite
|
Sign up to set email alerts
|

Identification and treatment of depression of older adults in primary care: findings from the São Paulo Ageing and Health Study

Abstract: Levels of treatment of depression in older adults receiving care in the FHP is very low compared to treatment rates of diabetes and hypertension. Collaborative care effectiveness trials for the treatment of depression in the FHP are needed to improve the quality of depression care for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
0
10
0
2
Order By: Relevance
“…Screening may be a useful tool for identifying depressed persons with diabetes, because previous research has shown that the uptake of depression care is low, due to poor depression recognition by healthcare professionals in standard care [1517]. Another possibility for the low uptake of depression care is that many depressed persons with diabetes do not have a need for psychological care.…”
Section: Introductionmentioning
confidence: 99%
“…Screening may be a useful tool for identifying depressed persons with diabetes, because previous research has shown that the uptake of depression care is low, due to poor depression recognition by healthcare professionals in standard care [1517]. Another possibility for the low uptake of depression care is that many depressed persons with diabetes do not have a need for psychological care.…”
Section: Introductionmentioning
confidence: 99%
“…A National Health Survey-Brazil (2013) found a higher prevalence of depression diagnosis in people aged between 60 and 64 years (11.1%) and 65 and 74 years (9.9%) compared with the other age groups over 18 years (3.9–8.8%) [ 5 , 6 ]. Moreover, a study with older adults living in poor neighbourhoods in São Paulo, Brazil, found that 5% of this population met the criteria for a depressive episode and that identification of depression symptoms was low, with less than 5% of those who met these criteria being diagnosed by primary care services [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, mental health care is still not adequately integrated into the primary care services, and there is a scarcity of trained mental health resources working in the public system [ 8 ]. Thus, depression in later life is often unidentified and left untreated despite the vast array of adverse social, economic and health consequences [ 7 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Scazufa et al [24] compared the depression identification and treatment rates with those of diabetes and hypertension among elderly individuals served in primary care [25]. Of 1558 participants, 4.8 % were diagnosed with depression based on ICD-10 criteria.…”
Section: Hypertensionmentioning
confidence: 99%